Lato-Lato Viral Games and Their Social Impact on Children - Khamim Zarkasih Putro (Journal of Contemporary Gender and Child Studies, 2022)
The lato-lato game is a traditional game with the current trend which is made of two pendulums tied to a string. The existence of lato-lato games helps children reduce playing gadgets so that children are not affected by the negative effects of playing gadgets. This paper aims to describe the social impact of playing lato-lato, especially on SD/MI-aged children. This research uses a qualitative descriptive approach with the method of literature study. The results of this study indicate that playing lato-lato can help in social development of children, because playing lato-lato is more fun when played together, so that children interact more with their friends than playing gadgets at home.